The past as prologue: The importance of history to the military profession - Hart Sinnreich, Richard (Cambridge University, 2013)
Exploring the usefulness of the study of history for contemporary military strategists, this volume illustrates the great importance of military history while simultaneously revealing the challenges of applying the past to the present. Essays from authors of diverse backgrounds--British and American, Civilian and Military--present an overwhelming argument for the necessity of the study of the past by today's military leaders in spite of these challenges. Part I examines the relationship between history and the military profession. Part II explores specific historical cases that reveal the repetitiveness of certain military problems.